Eco-friendly green synthesis of copper nanoparicles using leaf extract of medicinal plant Jatropha gossypfolia - KALARANI, G.; BHARATHI; LEKHA, N. CHANDRA; SELVIPRIYA (International Journal of Psychosocial Rehabilitation, 2020)
–In this study, we have synthesized copper nanoparticles (CuNPs) from the plant Jatropha gossypfolia leaf extract. The formation of CuNPs were confirmed by various spectroscopic and microscopic techniques such as UV, FT-IR, AFM and SEM –EDAX. Phytochemical screening studies of the plant extract were performed which indicated the presence of flavanoids, phenols, saponins, tannins, alkaloids, phytates and steroids. The surface morphology of the synthesized copper nanoparticles was examined as spherical in shape with an average diameter varied from 28-86nm by SEM analysis. The copper nanoparticles have good potential of antioxidant activity.